Blob-B-Gone: a lightweight framework for removing blob artifacts from 2D/3D MINFLUX single-particle tracking data - Vogler, Bela T. L.; Reina, Francesco; Eggeling, Christian (Frontiers in Bioinformatics, 2023)
We introduce Blob-B-Gone, a lightweight framework to computationally differentiate and eventually remove dense isotropic localization accumulations (blobs) caused by artifactually immobilized particles in MINFLUX Single Particle Tracking (SPT) measurements. This approach uses purely geometrical features extracted from MINFLUX-detected single particle trajectories, treated as point clouds of localizations. Employing k-means++ clustering we perform single-shot separation of the feature space to rapidly extract blobs from the dataset without the need of training. We automatically annotate the resulting sub-sets, and finally evaluate our results by means of Principal Component Analysis (PCA), highlighting a clear separation in feature space. We demonstrate our approach, using two- and three-dimensional simulations of freely diffusing particles and blob artifacts, based on parameters extracted from hand-labelled MINFLUX tracking data of fixed 23nm bead samples and two-dimensional diffusing quantum dots on model lipid membranes. Applying Blob-B-Gone, we achieve a clear distinction between blob-like and other trajectories, represented in F1-scores of 0.998 (2D) and 1.0 (3D) as well as 0.995 (balanced) 0.994 (imbalanced). This framework can be straightforwardly applied to similar situations, where discerning between blob and elongated time traces is desirable. Given a number of localizations sufficient to express geometric features, the method can operate on any generic point clouds presented to it, regardless of its origin.